SUMBER DAYA MANUSIA DAN DORONGAN TERHADAP PERUBAHAN ORGANISASI - Walean, Ronny Hansje (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
The purpose of this paper is to encourage an organization to realize how crucial it is to consider the important of human resource and the organization changes for the success of an organization particularly in this era, the era of globalization. The intangible assets of a firm are its employees, therefore, proper planning for human resource can benefit the organization.   Human assets can assist HRD in determining their value to the bottom line. Change management entails thoughtful planning and sensitive implementation, and above all, consultation with, and involvement of, the people affected by the changes. If changes are forced on people normally problems arise, therefore, change must be realistic, achievable and measurable. These aspects are especially relevant to managing human resource change.